2017
DOI: 10.1590/1806-9282.63.03.252
|View full text |Cite
|
Sign up to set email alerts
|

Patient adherence to ischemic heart disease treatment

Abstract: Introduction:The effectiveness of the treatment of chronic diseases depends on the participation of the patient, influenced by different sociocultural factors, which are not fully recognized by the treatment routine. Objective: To search for some of these factors that hinder or facilitate adherence to treatment and use of healthcare resources, approaching patients with ischemic heart disease. Method: A cross-sectional study was conducted using face-to-face interviews. We applied semi-structured questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…If analyze modified affecting reasons, it could be suggested that too many prescribed medications with difficult regime of usage (twice or trice daily) with non-adequate outpatient supervision may significantly decrease adherence causing development of complications, that may lead to re-hospitalizations and cardiovascular death, which corresponds to literature data [13,14].…”
Section: Discussionmentioning
confidence: 70%
“…If analyze modified affecting reasons, it could be suggested that too many prescribed medications with difficult regime of usage (twice or trice daily) with non-adequate outpatient supervision may significantly decrease adherence causing development of complications, that may lead to re-hospitalizations and cardiovascular death, which corresponds to literature data [13,14].…”
Section: Discussionmentioning
confidence: 70%
“…To the best of our knowledge, this is the first study to introduce and examine the psychometric properties of such an instrument in a sample of caregivers of CHD patients. Previous research has underscored the importance of the caregivers' role in the care of these patients [31,32]; consequently, having a valid and reliable instrument available to quantify this support is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Medication adherence is the extent to which the patient adheres to the interval and dosage regimen of the drug prescribed to overcome the disease (Nobre and Domingues, 2017). It has a complex set of behaviours consisting of initiation, implementation, and termination phases (Rehman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%